ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PESERTA BPJS KESEHATAN MANDIRI DALAM MEMBAYAR IURAN BULANAN DI PUSKESMAS NAMU UKUR KECAMATAN SEI BINGAI KABUPATEN LANGKAT TAHUN 2018 - sinulinggaa, dianaa; Sari, Nur (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2019)
Compliance occurs when individual do the demand which is given because of she/he wants to receive the better reaction from the other individuals or groups. The scope of National Health Insurance Participants such a date December 31st 2016 that include as self-supporting categorical in all over Indonesia which is reached 5.060.927 peoples. In September 2017, BPJS which as the National Health Insurance Implementer states that it has deficit up to 9 billion. The goal of this research analyzed the factors that influence the compliance of BPJS self-supporting participants when they paid the month premium in Namu Ukur PUSKESMAS Sei Bingai Sub district Langkat Regency in 2018. The research type was analytic survey whereas by using cross-sectional approach. The sample amounted 185 based on probability sampling. The data collection is done by interview; the data analysis was bivariate that is done by using chi-square test with credibility level 95% (Î±=0,05). The research result showed that reciprocity variable include good category and the activeness for pay the premium (80,1%), Validation Social include good category and the activeness for pay the premium (86,6%), Commitment / Consistency (80,8%), Friendship/liking (91,6%), Authority (81,1%). The most related variable is reciprocity which got the value exp (B) 270,190 that means it has the opportunity for having the compliance to pay the premium as many as 270,190. It is suggested for Langkat Regency BPJS so that constant to evaluate the implementation of National Health Insurance and make the coordination with health facility that have cooperative with BPJS in order to keep the compliance quality so that National Health Insurance Participants feel positive reciprocal from their activeness pay the premium.